British prints from the machine age : rhythms of modern life 1914-1939 - Ackley, Clifford S; Coppel, Stephen; Museum of Fine Arts, Boston; Metropolitan Museum of Art (New York, N.Y.); Wolfsonian-Florida International University (London : Thames and Hudson, 2008)
This book examines the impact of avant-garde Continental influences on British printmaking in the years stretching from the First World War to the outbreak of the Second. Highlighting works by thirteen artists, it focuses in particular on the dynamic imagery of early followers of Italian Futurism and British Vorticism, and on the works of artists associated with the Grosvenor School. The book features lithographs, etchings, woodcuts and linocuts.
Collecting Modernists Prints: The Garfields / Stephen Coppel -- Rhythms of Modern Life / Clifford S. Ackley -- Vorticism and Abstraction -- World War -- Speed and Movement -- Urban Life/Urban Dynamism -- Sport -- Industry and Labor -- Entertainment and Leisure -- Natural Forces -- The History and Characteristics of Linoleum Block Prints / Stephanie M. Lussier -- Materials and Techniques of the Grosvenor School Artist / Rachel Mustalish
Artists: Henri Gaudier-Brzeska-- Edward Wadsworth-- Claude Flight-- David Bomberg-- E. McKnight Kauffer-- Cyril E. Power-- C.R.W. Nevinson-- Paul Nash-- Sybil Andrews-- Lill Tschudi-- Leonard Beaumont-- Eileen Mayo-- William Greengrass
Published on the occasion of the exhibition organized by the Museum of Fine Arts, Boston, January 30-June 1, 2008; Metropolitan Museum of Art, September 23-December 14, 2008; The Wolfsonian-Florida International University, November 21, 2009-February 28, 2010
Includes bibliographical references (pages 222-223)
Keywords: Prints, British -- 20th century; Futurism (Art) -- Great Britain; Cubism -- Great Britain; Technology in art